PERSEPSI MASYARAKAT TERHADAP PROFIL DAERAH ALIRAN SUNGAI CITARUM HILIR (Kasus di Sungai Citarum Hilir, Desa Pantai Bahagia, Kecamatan Muara Gembong, Kabupaten Bekasi, Provinsi Jawa Barat) - Langkeru, Alan Yonathan; Muttaqin, Zainal; Salampessy, Messalina L. (Universitas Nusa Bangsa, 2022)
The problem of the Citarum Hilir watershad is dominated by the low awareness of the community and local government for natural preservation. Therefore it is necessary to conduct a perception assessment to support the success of activities in the preservation of the Citarum Hilir watershad. This study aims to describe people's perceptions of sub-watershed management and their functions. The sampling method is a purposive sampling technique. The data collection method was carried out by in-depth interviews with 30 respondents. Data analysis was carried out using a Likert Scale and described in the form of the percentage (%) with the highest number of answers. The results showed that the public's perception of the watershed was included in the category of quite understanding and very understanding (50%) that the watershed is a stream that surrounds and merges with the river and its tributaries. The community's perception of the condition of the watershed is in the category of very understanding (57%) that the condition of the watershed often experiences inundation in several parts of the downstream of the village and a lot of waste. The community's perception of the impact of watershed damage is included in the very understanding category (100%). The community's perception of the utilization of watershed resources is included in the category of very understanding (70%). In the category of very understanding (63%) of using the watershed as a means of transportation, irrigation of rice fields and daily needs. The public's perception of the watershed profile is in the understanding category with a score of 4.0.